2019
DOI: 10.1111/famp.12445
|View full text |Cite
|
Sign up to set email alerts
|

Therapist Interventions Associated with Productive Emotional Processing in the Context of Attachment‐Based Family Therapy for Depressed and Suicidal Adolescents

Abstract: Productive emotional processing is considered a key change mechanism in attachmentbased family therapy (ABFT). This study examined the impact of attachment-based family therapy therapist interventions aimed to promote productive emotional processing of primary adaptive emotions in a sample of 30 depressed and suicidal adolescents who had participated in a larger randomized clinical trial. Results of sequential analyses revealed that relational reframes and therapists' focus on primary adaptive emotions were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…With respect to facilitating emotional expression and flow , our analysis demonstrated that supportive emotional expression techniques such as listening and empathy could facilitate the expression and relief of the families’ emotions and pain. This is similar to the results of prior studies ( Sundet, 2011 ; Lovgren et al, 2019 ; Tsvieli et al, 2019 ). Wang et al’s studies reported poorer family interpersonal communication in Chinese families with a depressed family member than in Chinese families without depressed family members, and after systematic family therapy, not only were depressive symptoms relieved, but family communication was also improved ( Wang et al, 2013 ; Li et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With respect to facilitating emotional expression and flow , our analysis demonstrated that supportive emotional expression techniques such as listening and empathy could facilitate the expression and relief of the families’ emotions and pain. This is similar to the results of prior studies ( Sundet, 2011 ; Lovgren et al, 2019 ; Tsvieli et al, 2019 ). Wang et al’s studies reported poorer family interpersonal communication in Chinese families with a depressed family member than in Chinese families without depressed family members, and after systematic family therapy, not only were depressive symptoms relieved, but family communication was also improved ( Wang et al, 2013 ; Li et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…In family therapy, techniques that have been proposed to be effective include posing circular questions, creating genograms, reframing, making metaphors, expressing acknowledgment, using reflecting teams, playing video games, reformulating, and giving feedback ( Sundet, 2011 ; de Leon, 2018 ; Earl, 2018 ; Larner, 2018 ; North et al, 2018 ). In attachment-based family therapy for depressed adolescents, previous research reported that encouraging clients’ affect, focusing on adolescents’ unmet attachment/identity needs, relational reframing, and focusing on clients’ primary adaptive emotions allowed therapists to promote adolescents’ productive emotional processing and improve the quality of their attachment with their parents, in turn promoting relief of their depressive symptoms ( Diamond et al, 2002 ; Ewing et al, 2015 ; Tsvieli et al, 2019 ). In psychodynamic therapy of adolescent depression, clients have considered self-exploration and discussion of issues in their daily lives to be helpful ( Lovgren et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that aspects of the therapist's interventions influence therapeutic response. For example, focusing on unmet attachment needs and reframing psychological problems in terms of relational issues supports the processing of vulnerable emotions in adolescents participating in family therapy (Tsvieli et al, 2020), and stronger parent-therapist alliances are associated with increased attachment-promoting behaviour in parents (Feder and Diamond, 2016). These findings highlight the importance of considering therapist variables as a mechanism of change in attachment-based family therapy.…”
Section: Attachment Representations and Discoursementioning
confidence: 86%
“…In the present study, following adjustment for sociodemographic data, variables related to student life, and events in the students' lives, an important association was found between distinct patterns of parental bonding styles and psychological issues in these medical students. Therefore, it is possible that preventive and therapeutic inter-ventions related to the attachment theory, for example, attachment-based family therapy [38], family constellations [39], and therapy of bonding disorders and trauma [33], among others, could benefit medical students in their personal and academic career. These subject merits further investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%